Randomized controlled trials of iron chelators for the treatment of cardiac siderosis in thalassaemia major - Baksi, A. John; Pennell, Dudley J. (Frontiers in Pharmacology, 2014)
In conditions requiring repeated blood transfusion or where iron metabolism is abnormal, heart failure may result from accumulation of iron in the heart (cardiac siderosis). Death due to heart failure from cardiac iron overload has accounted for considerable early mortality in β-thalassemia major. The ability to detect iron loading in the heart by cardiovascular magnetic resonance using T2* sequences has created an opportunity to intervene in the natural history of such conditions. However, effective and well tolerated therapy is required to remove iron from the heart. There are currently 3 approved commercially available iron chelators: deferoxamine, deferiprone and deferasirox. We review the high quality randomised controlled trials in this area for iron chelation therapy in the management of cardiac siderosis.